3-D negotiation : - Lax, David A. (Harvard Business School Press, 2006)
When discussing being stuck in a "win-win vs. win-lose" debate, most negotiation books focus on face-to-face tactics. Yet, table tactics are only the "first dimension" of David A. Lax and James K. Sebenius' pathbreaking 3-D Negotiation (TM) approach, developed from their decades of doing deals and analyzing great dealmakers. Moves in their "second dimension"—deal design—systematically unlock economic and noneconomic value by creatively structuring agreements. But what sets the 3-D approach apart is its "third dimension": setup. Before showing up at a bargaining session, 3-D Negotiators ensure that the right parties have been approached, in the right sequence, to address the right interests, under the right expectations, and facing the right consequences of walking away if there is no deal. This new arsenal of moves away from the table often has the greatest impact on the negotiated outcome. Packed with practical steps and cases, 3-D Negotiation demonstrates how superior setup moves plus insightful deal designs can enable you to reach remarkable agreements at the table, unattainable by standard tactics.